Living Cell Manipulation, Manageable Sampling, and Shotgun Picoliter Electrospray Mass Spectrometry for Profiling Metabolites - Gholipour, Yousef (2013)
A modified cell pressure probe and an online Orbitrap mass spectrometer were used to sample in situ plant single cells without any additional manipulation. The cell pressure probe, a quartz capillary tip filled with an oil mixture, was penetrated to various depths into parenchyma cells of tulip bulb scale, followed by a hydraulic continuity test to determine the exact location of the tip inside target cells. The operation was conducted under a digital microscope, and the capillary tip was photographed to calculate the volume of the cell sap sucked. The cell sap sample was then directly nebulized/ionized under high-voltage conditions at the entrance of the mass spectrometer. Several sugars, amino acids, organic acids, vitamins, fatty acids, and secondary metabolites were detected. Because picoliter solutions can be accurately handled and measured, known volumes of standard solutions can be added to cell sap samples inside the capillary tip to be used as references for metabolite characterization and relative quantitation. The high precision and sensitivity of the cell pressure probe and Orbitrap mass spectrometer allow for the manipulation and analysis of both femtoliter cell sap samples and standard solutions.